2006
DOI: 10.1021/tx0601105
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen, a Seleno-organic Antioxidant, as an Electrophile

Abstract: Ebselen [2-phenyl-1,2-benzisoselenazol-3(2H)-one], a seleno-organic compound showing glutathione peroxidase-like activity, is one of the promising synthetic antioxidants. In the present study, we investigated the electrophilic potential of this antioxidant and established the mechanism of the cysteine-targeted oxidation of protein. In addition, using ebselen as an electrophilic probe, we characterized the cysteine residues required for posttranslational modification into an electrophile sensor protein in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 47 publications
5
116
1
1
Order By: Relevance
“…It appeared that the reactivities of the cysteines in human Keap1 are different from the corresponding cysteines in mouse Keap1 [112][113][114][115]117]. Despite some uncertainty regarding the exact order of the reactivity of the cysteine residues towards different electrophiles, Cys-151 (located in the BTB domain) was identified as the most reactive nucleophilic site in human Keap1 [113,117]. It is conceivable that multiple cysteines in Keap1 can be modified by different inducers and it is likely that sites of sulfhydryl modification may vary among the different chemical compound classes and across species [118].…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
“…It appeared that the reactivities of the cysteines in human Keap1 are different from the corresponding cysteines in mouse Keap1 [112][113][114][115]117]. Despite some uncertainty regarding the exact order of the reactivity of the cysteine residues towards different electrophiles, Cys-151 (located in the BTB domain) was identified as the most reactive nucleophilic site in human Keap1 [113,117]. It is conceivable that multiple cysteines in Keap1 can be modified by different inducers and it is likely that sites of sulfhydryl modification may vary among the different chemical compound classes and across species [118].…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
“…Ebselen, 31, has variously been reported as a phase 2 enzyme inducer that acts through the Nrf2 pathway (50). It has been shown to decrease basal ROS and the flux induced by 4-hydroxynonenal.…”
Section: Class F Compoundsmentioning
confidence: 99%
“…Regardless, these results indicate C151 is extremely reactive toward these three chemoprevention agents. Located in the BTB domain of Keap1, sitedirected mutagenesis studies have indicated that C151 is essential for inhibition of Keap1-dependant ubiquitination and degradation of Nrf2 in response to all tested agents, including tBHQ and sulforaphane [3], NEPP11, an endogenous neurite outgrowth-promoting prostaglandin [34], and ebselen, a seleno-organic drug [35]. Taken together, C151 plays a critical role in the Keap1-Nrf2 signaling system, and our results support the view that C151 is a target for Nrf2 activation by Michael addition reaction acceptors that function as ARE inducers.…”
Section: Modification Sites Of Human Keap1 By Electrophilesmentioning
confidence: 99%